Social readiness of adaptation technologies. (10th October 2019) - Bellamy, Rob
Abstract: Despite growing recognition that Europe must adapt to climate variability and change, there is still limited evidence of adaptation implementation. At the same time, despite knowing that successful adaptation will be contingent on societal factors just as much as on technical ones, there has been very little research into social perceptions of adaptation technologies. To address this gap, I undertake an interdisciplinary synthesis of stable beliefs and values about technology—those that are less susceptible to change across different situations—from five major but hitherto disconnected theoretical perspectives on perceptions of technology: the psychometric paradigm, the technology control dilemma, cultural theory, technology acceptance models, and responsible innovation. Four common dimensions of perception were identified: knowledge of technology, scope of technological projects, impacts of technology, and trust in the control of technology. These dimensions can be used to develop a concept of and framework for social readiness, whereby aspects of adaptation technologies that are likely to be perceived negatively or positively, and by whom, can be identified. This is by no means a panacea to the challenges of adaptation implementation, but one that contributes to and would join in constructive exchange with wider efforts to evaluate adaptation technologies. I end this review by discussing the need for bridging the gap between opposing epistemic cultures that favor different styles of knowledge production around adaptation technology perception. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : Stable beliefs and values that (a) are associated with negative or positive perceptions of technologies and (b) correspond to elementary social groups and their commitments to particular sociotechnical systems